ANALYSING THE INFLUENCE OF PRODUCT PLACEMENT IN HEALTHY LIFESTYLE VLOGGER CONTENT - Wisudawati, Lidya Hesliony; Iskandar, Budi Permadi (Journal of Business and Management, 2018)
Abstract. Social Media has become a part of everyday life and most of its users are active on YouTube. YouTube, as the most popular site, is a video sharing platform where one of its content is a vlog. Based on the brand perspective, vlog is an effective marketing approach. Currently, the number of vlogs in the health and fitness category has increased. The increase of that number happens because consumers seek motivation regarding healthy lifestyle by watching vlogs. In line with the growing popularity of health and fitness vlogs, advertisers bold to place products in this kind of content. Product placement will help to speed up the sales process. The appearance of product placement means brand endorsement is being used and requires the attention of healthy lifestyle vloggers related to the content brand endorsement they use to market the product. Therefore, this research aimed to analyze the influence caused by product placement in healthy lifestyle vlogger vlog content by using qualitative approach which is content analysis. This research was conducted using video transcripts of 10 healthy lifestyle vloggers that have been coded and reviewed based on Match-Up Hypothesis and Para-Social Interaction. The study found that product placement has an influence on healthy lifestyle vlogger content and match-up hypothesis is the most dominant influenced by product placement. Match-up hypothesis relating to product information, honesty, and mentioning brand. The explanation of these two factors will be further explained in the study. The results of the study are important and useful not only for healthy lifestyle vloggers in building their popularity but also for advertisers in using vlogs as a way to market their products.Keywords: content brand endorsement, healthy lifestyle vloggers, match-up hypothesis, para-social interaction, product placement, social media, vloggers, YouTube